2018
DOI: 10.1002/sim.7947
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian varying coefficient kernel machine regression to assess neurodevelopmental trajectories associated with exposure to complex mixtures

Abstract: Exposure to environmental mixtures can exert wide-ranging effects on child neurodevelopment. However, there is a lack of statistical methods that can accommodate the complex exposure-response relationship between mixtures and neurodevelopment while simultaneously estimating neurodevelopmental trajectories. We introduce Bayesian varying coefficient kernel machine regression (BVCKMR), a hierarchical model that estimates how mixture exposures at a given time point are associated with health outcome trajectories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…However, the epidemiologic literature on interactions between Cu and either Mn or Pb is sparse. One recent epidemiologic study of children in Mexico City used BKMR and reported a similar interaction between Cu and Pb and neurobehavior, where higher concentrations of Pb reduced the beneficial effect of Cu on infant neurodevelopment ( Liu et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the epidemiologic literature on interactions between Cu and either Mn or Pb is sparse. One recent epidemiologic study of children in Mexico City used BKMR and reported a similar interaction between Cu and Pb and neurobehavior, where higher concentrations of Pb reduced the beneficial effect of Cu on infant neurodevelopment ( Liu et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the epidemiologic literature on interactions between Cu and either Mn or Pb is sparse. One recent epidemiologic study of children in Mexico City used BKMR and reported a similar interaction between Cu and Pb and neurobehavior, where higher concentrations of Pb reduced the beneficial effect of Cu on infant neurodevelopment (Liu et al 2018). Despite several differences in study design, including exposure timing (prenatal versus adolescent), age at outcome assessment (6-24 months versus adolescence), and sources of contaminants (unknown versus ferroalloy industry), this finding of a Cu-Pb interaction using BKMR is consistent with ours.…”
Section: Environmental Health Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…time series or longitudinal data). The BKMR approach [50] can handle repeated measures, and the more recently developed Bayesian varying coefficient kernel machine regression (BVCKMR) is designed to estimate the mixture effects on outcome trajectories [51]. These two approaches characterize the exposure-response surface and provide visualizations of the interaction effects between mixture components for longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, statistical programs would be invoked to assess the overall risk from such a mixture of levels. Such developments are currently being addressed by research examining multiple neurotoxin effects and also mathematical frameworks that can handle such complex mixtures [120,121].…”
Section: Discussionmentioning
confidence: 99%